Konsep al-Nabī al-Ummī dan Implikasinya pada Penulisan Rasm - Eva Nugraha (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2012)
The concept of al-nabī al-ummī has existed since the beginning of Islam. The Prophet Muḥammad declared himself as al-nabī al-ummī, both in the Qur’ān and Ḥaḍth. However, most Muslim scholars disagree if al-ummī means illiterate. Through the linguistic and historical approach, this paper would like to test the question ”whether the implication of al-nabī alummī concepts in the Qur’ānic orthography (rasm) is tawqīfī or iṣṭilāḥī.DOI: 10.15408/ref.v13i2.901